Successful governance initiatives and the best practices - India. Planning commission (New Delhi, 2003)
Prepared by the State Plans Division of the Planning Commission in collaboration with the Human Development Resource Centre, this volume compiles successful government initiatives from across the country in the areas of land, water and livelihood; human development and social services; and public interface with government.
Keywords: Economic development-India